128 Systematic monitoring of etco2 in procedural sedations: a relevant medical practice or not?. (20th August 2018) - Asselin, Genevieve; Drolet, Renée; Coulombe, Martin; Rhainds, Marc
Abstract : Objectives: Clinical monitoring of all patients should be performed during procedural sedation to prevent possible complications including airway obstruction, apnea and hypotension. Capnography, which measures end-tidal carbon dioxide (ETCO2), is a non-invasive monitoring method that provides information about metabolic, circulatory and respiratory activities. ETCO2 could be added to other standard monitoring during procedural sedation as measurements of blood pressure, pulse, respiration, and oxygen saturation to allow early detection of critical respiratory incidents. This project aims to determine if ETCO2 should be mandatory in our hospital to ensure the safety of care during procedural sedation. Method: Literature search was conducted in indexed databases and grey literature between January 1 st 2005 and April 12th 2018. Systematic reviews (SRs), clinical practice guidelines (CPGs) and primary studies on the use of ETCO2 monitoring in adults or children under procedural sedation were retrieved. Two reviewers independently performed selection, quality assessment and data extraction. Outcomes included respiratory depression rate, interventions needed to respiratory support, cardiac arrest, desaturation, hypotension, antagonist administration and false alarms. Two hospital databases were consulted to estimate the volume of procedural sedations performed during the financial year 2016–2017. Reported accidents were also retrieved from hospital database between January 1 st 2012 and March 21 st 2018. Results: Six SRs and 26 CPGs were analyzed. Although CPGs recommendations are based on poor scientific evidence, they mainly targeted propofol administration or deep level sedation for the use of ETCO2. Results from meta-analyses (n=4) suggest a statistically significant lower risk of desaturations with the ETCO2 in addition to standard monitoring compared to standard monitoring. Heterogeneity between studies (desaturation definitions, procedures, depth of sedation, sedatives, oxygen administration) invites caution regarding the interpretation of these data. Effects of ETCO2 use on other outcomes remain undetermined. No serious complication with ETCO2 use during procedural sedation was reported. More than 30 000 interventions with procedural sedation are performed each year in our hospital, mainly related to emergency, gynecologic, radiologic and endoscopic procedures. The addition of ETCO2 to clinical monitoring was only found in the emergency department. Adverse events during procedural sedations were reported in two cases according to the hospital database. Conclusions: The addition of ETCO2 to standard monitoring could possibly improve clinical management of procedural sedations by reducing desaturation events. However, the clinical significance to prevent such events on serious respiratory outcomes is unclear. Because results mainly refer to deep sedation with propofol, no firm conclusion can be drawn regarding ETCO2 use in case of minimal to moderate procedural sedations. Considering the risk of unnecessary medical interventions, clinicians should be advised to use ETCO2 in specific procedural sedations instead of systematically.